Asymmetries in Risk Premia, Macroeconomic Uncertainty and Business Cycles - Christoph Görtz; Mallory Yeromonahos (Center for Economic Studies and ifo Institute (CESifo), 2019)
A large literature suggests that the expected equity risk premium is countercyclical. Using a variety of different measures for this risk premium, we document that it also exhibits growth asymmetry, i.e. the risk premium rises sharply in recessions and declines much more gradually during the following recoveries. We show that a model with recursive preferences, in which agents cannot perfectly observe the state of current productivity, can generate the observed asymmetry in the risk premium. Key for this result are endogenous fluctuations in uncertainty which induce procyclical variations in agent's nowcast accuracy. In addition to matching moments of the risk premium, the model is also successful in generating the growth asymmetry in macroeconomic aggregates observed in the data, and in matching the cyclical relation between quantities and the risk premium.
Keywords: E20; E30; G10; 330; risk premium; business cycles; Bayesian learning; asymmetry; uncertainty; nowcasting